Variability of Known Exoplanet Host Stars Observed by TESS - Emilie R. Simpson; Tara Fetherolf; Stephen R. Kane; Joshua Pepper; Teo Močnik; Paul A. Dalba (The Astronomical Journal)
Both direct and indirect methods of exoplanet detection rely upon detailed knowledge of the potential host stars. Such stellar characterization allows for accurate extraction of planetary properties, as well as contributing to our overall understanding of exoplanetary system architecture. In this analysis, we examine the photometry of 264 known exoplanet host stars (harboring 337 planetary companions) that were observed during the Transiting Exoplanet Survey Satellite (TESS) Prime Mission. We identify periodic signatures in the lightcurves of these stars and make possible connections to stellar pulsations and their rotation periods, and compare the stellar variability to the published planetary orbital periods. From these comparisons, we quantify the effects of stellar variability on exoplanet detection, confirming that exoplanets detection is biased toward lower variability stars, but larger exoplanets dominate the population of exoplanets around variable stars. Exoplanet detection methods represented among these systems are distinct between stellar spectral types across the main sequence, though notable outliers exist. In addition, biases present in both the sourced data from TESS and the host star selection process, which strongly influences the representation of both stellar and planetary characteristics in the final populations. We also determine whether the host stars photometric variability affects or mimics the behavior or properties of the system’s planets. These results are discussed in the context of how the behavior of the host star is responsible for how we observe exoplanet characteristics, most notably their radii and atmospheric properties, and how the activity may alter our measurements or impact the evolution of planetary properties.